Pesticide residues as environmental contaminants in foods in Nepal - Koirala, Pramod; Khadka, Damodar B.; Mishra, Arunananda (Journal of Agriculture and Environment, 2007)
This paper reviews the occurrence of pesticides in foods in Nepal during 1995-2004. A total of one thousand and thirty four samples of different food commodities were analyzed for detection of organochlorines (DDT, BHC) and organophosphorus (malathion, parathion, methyl parathion) pesticides. Among all samples analysed 12% samples were detected with the residues of pesticides which included Malathion (3.9%), BHC (3.1%), Methyl parathion (2.8%), DDT (1.8%) and Parathion (0.3%). Commodity- wise detection of pesticide residues showed the highest level of contamination in root vegetables (11.9%) followed by leaf vegetables (10.9%). Therefore, there is a threat of pesticide residues in foods and may endanger to public health. Government efforts to control misuse of pesticides is not sufficient, therefore, the concerned stakeholders have the shared responsibility to solve it. There is a good scope of working with appropriate intervention measures in this area for NGOs, INGOs, academic institution to prevent the pesticide pollution in food. The Journal of AGRICULTURE AND ENVIRONMENTVol. 8, 2007, pp. 96-100